1991
DOI: 10.1111/j.1528-1157.1991.tb04679.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial, Intraaxial, Space‐Occupying Lesions in Patients with Intractable Partial Seizures: An Anatomoclinical, Neuropsychological, and Surgical Correlation

Abstract: Fifty of approximately 250 patients evaluated for intractable partial seizures were shown to have a space-occupying lesion detected with radiographs and/or neuroimaging. Twenty-eight males and 22 females had a mean age at seizure onset of 13 years and a mean duration of seizures of 11 years. All patients had closed-circuit television with EEG monitoring and complete neurologic and neuropsychological assessment. Findings were correlated with lesion location and surgical data. Twenty-seven lesions (54%) were loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
6

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(71 citation statements)
references
References 33 publications
2
62
1
6
Order By: Relevance
“…Different surgical approaches have been used varying from simple lesionectomy to total lobectomy including the hyppocampus and amygdala. In some series as ours the inclusion of the mesial temporal structures didn't promote a better prognosis 7,14,15 while in others extensive resections implied in control of the seizures 3,16,17 . Studies have identified incomplete tumor resections or tumor recurrences as a important cause of a poor postoperative seizure control 8,[18][19][20] .…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different surgical approaches have been used varying from simple lesionectomy to total lobectomy including the hyppocampus and amygdala. In some series as ours the inclusion of the mesial temporal structures didn't promote a better prognosis 7,14,15 while in others extensive resections implied in control of the seizures 3,16,17 . Studies have identified incomplete tumor resections or tumor recurrences as a important cause of a poor postoperative seizure control 8,[18][19][20] .…”
Section: Discussion Discussionmentioning
confidence: 99%
“…20% of patients who undergo surgical treatment of temporal lobe medically refractory epilepsy [2][3][4] . Due of the benign nature of these lesions, recurrent, often refractory epilepsy, epileptic seizures are the usual presentation of these lesions, mass effect signs or bleeding are characteristically absent in this setting.…”
mentioning
confidence: 99%
“…Surface EEG is characterized by a higher incidence of interictal spikes compared to HS (89). Several authors have noted also that in patients with lesions interictal spikes may be more widespread (89,90) and may even occur bilaterally independent (91). These features are therefore not necessarily a contradiction to resection of the lesion.…”
Section: General Considerationsmentioning
confidence: 99%
“…This is supported by good outcomes in this patient group after lesionectomy. In a study published by Boon et al (90) Invasive recordings may be required in patients with a single lesion if seizure patterns recorded by surface EEG raise doubts that the lesion is indeed causing the epilepsy. Schiller et al (80) showed that 20 of 22 (90%) lesional patients with nonlocalizable surface EEG findings, but congruent intracerebral nionitoring and MRI results, were seizure-free after surgery.…”
Section: General Considerationsmentioning
confidence: 99%
“…When the peritumoural tissue removal is not satisfactory, postoperative seizure control remains effectively unchanged [107,108,9,106,109,58]. Image-guided stereotactic lesional resection achieves a longterm seizure-free outcome in 57% of cases [108] whereas the inclusion of peritumoural tissues in the resection volume raised this metric beyond 80% [110,111]. The realization that the peritumoural environment is critical in the promotion of most epileptic manifestations has prompted the use of intraoperative electrocorticography in cases of low grade gliomas, in particular, to increase the likelihood of capturing those responsible cortical areas in the resection volume [112][113][114][115][116].…”
Section: Surgerymentioning
confidence: 99%